The Influence of Madrasah Head Leadership Style and Teacher Self-Motivation on Teacher Performance - Azizah, Wafik; Suryani, Eva; Septaria, Vera (CV. Strata Persada Academia, 2024)
The purpose of this study is to investigate the impact of the leadership style of the Madrasah Head and the level of self-motivation of teachers on the overall performance of teachers at MIN 7 South Solok. The purpose of this study is to (1) Gain an understanding of the leadership style of the Madrasah Head and the impact of teacher self-motivation on the performance of teachers at MIN 7 South Solok. (2) Determine the extent to which the leadership style of the Madrasah Head has an impact on the classroom performance of teachers at MIN 7 South Solok. (3) Determine the extent to which self-motivated teachers have an impact on the overall performance of teachers at MIN 7 South Solok (4) Being aware of the impact that the leadership style of the Madrasah Head and the level of self-motivation of teachers have on the overall performance of teachers at MIN 7 South Solok. By utilizing SPSS for Windows 23, descriptive analysis and inductive analysis are used in the process of data analysis. The study's findings show that the Madrasah Head's leadership style significantly impacts MIN 7 South Solok teachers' performance. At MIN 7 South Solok, teachers' self-motivation has a significant effect on their performance. At MIN 7 South Solok, the Madrasah Head's leadership style and teachers' self-motivation work together to impact their performance significantly.